EFEKTIVITAS PENYULUHAN ANTIKORUPSI DENGAN PENDEKATAN PSIKORELIGIUS DALAM MENGEMBANGKAN NILAI-NILAI INTEGRITAS SISWA - Radhiya Bustan; Liana Mailani (Integritas: Jurnal Antikorupsi, 2022)
The experience of online learning during the Covid-19 pandemic led to an increase in cases of deception by high school students. For this reason, providing psycho-religious-based anti-corruption counseling to develop integrity and character values is one way to prevent corruption. The subjects of this study were 25 students of the student council (OSIS) at State Senior High School 1 Sukatani, West Java. This research was conducted with a mixed research method. Based on qualitative and quantitative data analysis, it obtained data showing that anti-corruption counseling with a psycho-religious approach through lectures, discussions (FGD), case studies, watching movies, creating e-flyers and presentations, as well as drafting action plans, can be effective to develop student integrity values. This program can be a model for preventing corruption in senior high schools, which can be carried out with either offline or online methods.